Prevalence of different gallbladder pathologies and usefulness of mucin histochemistry in early diagnosis of metaplasia and carcinoma of gallbladder - Joydip Sen; Suchismita Chakrabarti; Urvee Sarkar; Saugata Kumar Bhattacharya; Ruplekha Mitra Mustaphi (Asian Journal of Medical Sciences, 2024)
Background: Non-neoplastic and neoplastic diseases of gallbladder are most prevalent in northern and north-eastern states of Uttar Pradesh, Bihar, Orissa, West Bengal, and Assam in India. Chronic cholecystitis, the most common pathology of gallbladder is often associated with metaplasia of epithelium, leading to increased susceptibility to malignant transformation. Along with histopathological examination, mucin histochemistry is useful in early detection of metaplasia and thereby predicting metaplasia-dysplasia-carcinoma sequence. Aims and Objectives: The objective of this study was to estimate the prevalence of neoplastic and non-neoplastic diseases of gallbladder and to determine the usefulness of mucin histochemistry in early diagnosis of metaplasia and carcinoma of gallbladder. Materials and Methods: A cross-sectional observational study was conducted in R. G. Kar Medical College, Kolkata, over a period of 18 months. Total 401 cholecystectomy specimens were studied. In every case, following sequence of examinations was performed-gross examinations, histopathological examination, and mucin histochemistry. Results: All the available information was meticulously documented in tables and charts, software was used to calculate the statistical significance and efficacy of mucin histochemistry as a diagnostic tool. Conclusion: We found that mucin histochemistry is statistically significant and has positive predictive value in early diagnosis of metaplasia and carcinoma of gallbladder.